THE USE OF KEYWORD METHOD IN IMPROVING THE STUDENT’S READING COMPREHENSION IN MA AS'ADIYAH 170 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
Reading is one of the foremost imperative language abilities in expansion to three other language skills. Reading could be a great way to create and get it English. The securing of perusing aptitudes in remote language learning is considered a need. The objective of the investigate is to discover out the impact of using the Keyword Method to move forward the student’s reading comprehension and to discover out the student’s reaction toward utilizing Keyword Method to move forward the student’s reading comprehension. The investigate plan in this inquire about was pre-experimental by using a quantitative method. The instrument of this investigate was Test (Pre-test and Post-test) and a questionnaire. The inquire about comprised of 5 gatherings counting treatment. The sample of this investigate was class XI comprised of 34 understudies, 19 male s, and 15 females. The result of this investigate was shown the understudies ‘cruel score on pre-test was 53.12 and the cruel score of the post-test 75.12.  It concluded that the rate percentage in post-test was higher than the rate percentage in pre-test in teaching reading comprehension. It means that the was a significant improvement by using keyword method. The student's response through the questionnaire also had calculated on the finding, the result showed all the student's answered positive and all of them got 50-74.99 %. The main score students was 2.071 from 34 students which were categorized as responsive. Based on the score of the method, the researcher could conclude that the student's responsive and able to improve the student's in learning reading comprehension by using keyword method.